Efficacy of sofosbuvir and ledipasvir in an HCV+ gastro‐resected patient. (4th May 2017) - Taibi, C.; Tempestilli, M.; D'Avolio, A.; Garbuglia, A. R.; De Nicolò, A.; Montalbano, M.; D'Offizi, G.
Summary: What is known and objective: The second‐generation direct‐acting antivirals represented the first major turning point for the eradication of HCV infection in almost all settings of patients. However, no data were available on use in gastro‐resected patients. Case description: We report on a gastrectomized patient with chronic hepatitis C infection. She was treated with sofosbuvir and ledipasvir (SOF/LDV) for 12 weeks, with measurement of blood levels of the drugs. She obtained sustained virological response at week 12 and 24 without dose adjustment. What is new and conclusion: This case report can provide information useful for clinical practice in this set of patients and can open new perspectives in evaluating actual SOF/LDV bioavailability. Abstract : We describe the first reported case of treatment with direct antiviral agents in a gastrotomized patient. This report can provide information useful for clinical practice in this set of patients and can open new perspectives in evaluating Sofosbuvir/Ledipasvir bioavailability.